Framework para subsidiar a escolha de estratégias de prevenção da leishmaniose visceral - Queiroz, José Eric da Silva (2020)
Brazil is among the seven most endemic countries in the world for visceral leishmaniasis (VL). Thus, it is developing programs and encouraging interventions in order to reduce the impact of the disease. However, it is complex to Brazilian cities to decide about the most appropriate strategies for controlling zoonoses, given that the actions taken have not had the expected effect. The objective of this research is to develop a framework to assist in the selection of appropriate strategies for the prevention and control of VL through Multicriteria Decision Analysis (MCDA). The proposed methodology is organized in 3 stages: (i) identification and selection of the actors involved in the decision-making process, identification of the strategies currently used, and definition of criteria that must be considered when establishing the decision matrix; (ii) performance evaluation and weighting of the established criteria through the application of questionnaires and interviews and; (iii) application of the PROMSORT method to classify and prioritize VL prevention and control strategies. The proposed framework was applied in two different approaches: a) stakeholder consensus about the parameters; b) intersection of stakeholder assessment, being validated for Mossoró city. All strategies of the consensus approach were classified as adequate, but the sensitivity analysis revealed that five of them vary their classification, three of them were considered inadequate in 33.33% of the scenarios: control of the wandering canine population, vaccination and presence research of the vector. In the intersection approach, ten strategies were classified as strongly adequate and two as adequate. The sensitivity analysis demonstrated that two of them remained as highly adequate and the others varied their classifications, three of them were very sensitive as to the variation of the parameters, alternating from strongly adequate to little appropriate: euthanasia, proper disposal of corpses and control of the canine population wandering. Thus, only health education and environmental management strategies were classified as relevant, presenting stable behaviors in all simulations performed. Then it was noticed that the strategies related to the canine population axis were more fragile, therefore less indicated for the local context, while strategies directed to the environmental and human axes obtained more stable and pertinent results during the simulations realized. Between the two approaches, the intersection approach was considered more appropriate because it collected the individual point of view of the stakeholders, unlike the consensus assessment which the participants could influence each others judgment. To conclude, the proposed framework proved to be a tool ableto assist the decision-making process through a participatory approach, allowing the adaptation of the method to local contexts as a result of its application based on subjectivity